Genome-wide association study of elite Russian endurance athletes - Khabibova, S. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
It is well recognized that humans vary in their ability to achieve success in endurance sports and their predisposition is based on genetic factors. The aim of the study was to identify single nucleotide polymorphisms (SNPs) associated with elite endurance performance (maximal oxygen consumption rate, VO2max) in Russian endurance athletes using a genome-wide association study (GWAS) approach. VO2max was measured in 71 elite endurance Russian athletes (41 males and 30 females). HumanOmni1-Quad BeadChips (Illumina Inc, USA) were used for genotyping of 1,140,419 SNPs. We found that 568 SNPs were associated with VO2max in the combined cohort of endurance athletes (with P<0.001 adjusted for sex). Of those, two SNPs, namely SLC16A10 rs9400467 (P=0.0002653) and SLC38A1 rs10785611 (P=0.00013) are located in or near the genes expressions of which in the human skeletal muscle were previously reported to be linked with VO2max (Su et al. 2015). These genes are involved in the regulation of energy metabolism in skeletal muscles (SLC16A10) and glutamine uptake (SLC38A1). Interestingly, the rs9400467 polymorphism is also associated (P= 6,5*10-14) with tyrosine levels of human blood samples (Shin et al. 2014) and tyrosine ingestion improves aerobic performance. Our results suggest that at least SLC16A10 rs9400467 and SLC38A1 rs10785611 polymorphisms may predict human physical performance.